Construction and Analysis of Berber Text Corpus - Zayd, Khayi; Orobinska, Olena (My University, 2020)
This work is devoted to constructing a tool to analyze the different aspects of Berber languages. It is based on grammatical parameters of these languages. The text collection containing more than 500 texts that cover long historic period was collected. The corpus is free available and it will useful for further investigations on Tamazigh language. It was transformed into xml-format standardization goal. The corpus counts more than 200 000 of words. Based on the linguistic rules and statistic methods, original user interface and software prototype were developed by combining the technologies of web design and object programming in Python.
Keywords: Tamazight language; corpus linguistic; grammar rules; statistical methods; xml-structure; xml-format; Python; software